Significance of Mitral M-Mode Vp (Velocity Propagation) for Estimating Mitral Valve Area and Severity in Mitral Stenosis - Bertha Gabriela Napitupulu; Harris Hasan (ACI (Acta Cardiologia Indonesiana), 2019)
Background: Confirming mitral valve area (MVA) by planimetry is one of the standard procedures for assessing mitral stenosis but MVA were frequently need to be confirmed by other echocardiography parameters that only available in sophisticated centers. Our aim was to evaluate the significance of a simple mitral inflow color M-mode velocity propagation (Vp) for estimating MVA and MS severity.Methods: The best color view of MS jet were taken from apical 4 chamber, the nyquist limit were adjusted for aliasing the central highest velocity, then M-mode were applied to MV to calculate Vp by measuring the slope of the blue jet with the first aliasing velocity. MVA,PHT and mean transmitral gradient were analyzed with Pearson correlation and linear regression. Predictive discrimination value of Vp were analyzed by ROC.Results: Thirty one MS patients had mean MVA planimetry 0.99 ± 0.35 cm2 and mean Vp 64.49 ± 21.63 cm/s. Vp that were found to have a strong negative correlation with MVA (Spearman rho -0.865, p < 0.01). Vp had a good predictive discrimination value as from AUC 0.931. Vp were found to have a moderate correlation with MVA by PHT ( Spearman rho -0.621, p <0.01). Vp more than 55 cm/s had 93.8% sensitivity and 86.7% specificity to distinguish severe MS.Conclusions: By making use of the high temporal resolution of M-mode, a simple color Mitral M-Mode Vp were found statistically significant for estimating MVA severity in MS. Interventional decision for MS could also consider Vp for its strong correlation with MVA on MS, especially for helping on targeting moderate to severe MS in rural and limited centers.